Критерий функционирования автоматизированных диспетчеров распределенных датацентров - Ткачев, В. Н. (ХНУРЕ, 2011)
Criterion of functioning of the automated controllers of up-diffused datacenters is in-process resulted
Keywords: датацентр; big data